An analytic hierarchy process for quality action researches in education - Alvin Bersabal Barcelona (Institute of Advanced Engineering and Science, 2020)
Teachers are expected to engage in the praxis of educational reform, and one of the resurgent interests in the field of education is the conduct of action researches. In the Philippines and in many parts of the world, teachers are encouraged to perpetuate a culture of conducting action researches to improve the teaching and learning process. Considering the scant literature towards evaluation criteria for quality action researches, this exploratory-sequential mixed method study aims to determine the qualities that research experts perceive to be useful in evaluating action researches. Using Analytic Hierarchy Process, which is a multiple decision-making algorithm, research experts asserted that among the identified evaluation criteria, quality action researches should underscore its contribution to theory and practice, and require actionability and reflexivity among researchers and participants. The findings of this study may be of considerable interest and use to teachers, research authorities, and organizations who would like to ensure that teachers produce quality action research to improve educational practices.